Para início de conversa - Martins, Gleica Maria Correia; Bezerra, Sara Jane Cerqueira; Neves, Jhonatan David Santos das (Revista Interseção, 2023)
Revista Interseção, Palmeira dos Índios/AL, v. 5., n. 1, set. 2023, p. 1-4.